2020
DOI: 10.1187/cbe.20-04-0062
|View full text |Cite
|
Sign up to set email alerts
|

Fourteen Recommendations to Create a More Inclusive Environment for LGBTQ+ Individuals in Academic Biology

Abstract: This essay highlights recommendations to make academic biology more inclusive of LGBTQ+ individuals. These recommendations are drawn from the literature and the collective experience of the 26-member author team.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
79
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 101 publications
(179 reference statements)
1
79
0
Order By: Relevance
“…As we continue to seek widespread change in STEM education, future work should more closely examine the context within which instructors are working and how that affects their decision-making. In particular, the effects of context on the decision-making processes of instructors that identify with science persons excluded because of their ethnicity or race (PEERs) or who identify as LGBTQ+ should be explored as their experiences have significant implications for inclusion in STEM (Asai 2020;Cooper et al 2020). We will then be able to suggest beneficial changes at the institutional, departmental, and individual level that will help instructors adopt student-centered instructional practices in an evidence-based way.…”
Section: Resultsmentioning
confidence: 99%
“…As we continue to seek widespread change in STEM education, future work should more closely examine the context within which instructors are working and how that affects their decision-making. In particular, the effects of context on the decision-making processes of instructors that identify with science persons excluded because of their ethnicity or race (PEERs) or who identify as LGBTQ+ should be explored as their experiences have significant implications for inclusion in STEM (Asai 2020;Cooper et al 2020). We will then be able to suggest beneficial changes at the institutional, departmental, and individual level that will help instructors adopt student-centered instructional practices in an evidence-based way.…”
Section: Resultsmentioning
confidence: 99%
“…To explore the potential usefulness of the CSI framework in the unique context of biology, we used the CSI framework to explore Christianity, an identity that is not typically stigmatized 1 Some individuals have racial/ethnic identities that are hidden, and one should not assume a person's race/ethnicity based on physical appearance alone. Further, the gender identity that one identifies as may not be apparent from their physical appearance; this is particularly important for individuals who identify as nonbinary gender or transgender (Cooper et al, 2020a).…”
Section: Christianity As a Csi In Biologymentioning
confidence: 99%
“…Students suggested using online Fig. 3 Points along the process of obtaining an undergraduate research experience where we aimed to identify the rules of research 1 We recognize that not all students identify as gender binary (man or woman) (Cooper et al, 2020); however, there were too few students who identified as non-gender binary to include this category in the analysis. 2 We collapsed students who identify as Black or African American, Hispanic, Latino/a or of Spanish Origin, and American Indian or Alaska Native into one category, which we call Persons Excluded because of their Ethnicity or Race (PEER) (Asai, 2020).…”
Section: Finding Researchmentioning
confidence: 99%